2009
DOI: 10.1002/cbic.200900098
|View full text |Cite
|
Sign up to set email alerts
|

Functional Dissection of a Multimodular Polypeptide of the Pikromycin Polyketide Synthase into Monomodules by Using a Matched Pair of Heterologous Docking Domains

Abstract: The pikromyin polyketide synthase (PKS) in Streptomyces venezulae is comprised of a loading module and 6 extension modules which generate the corresponding 14-membered macrolactone product. PikAI is a multimodular component of this PKS and houses both the loading domain and the first two extension modules, joined by short intraprotein linkers. We have shown that PikAI can be separated into two proteins at either of these linkers, only when matched pairs of docking domains (DDs) from a heterologous modular phos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 42 publications
1
15
0
Order By: Relevance
“…This was illustrated by genetic manipulation of the producing strains for pikromycin and erythromycin. Separation of the naturally fused modules 1 and 2 reduced pikromycin production more than 1000-fold 82 . Conversely, fusion of the naturally in trans polypeptides DEBS1 and DEBS2, or DEBS2 and DEBS3, maintained or even enhanced erythromycin production relative to the wild type 83 .…”
Section: Protein-protein Interactions During Intermediate Transfer Bementioning
confidence: 99%
“…This was illustrated by genetic manipulation of the producing strains for pikromycin and erythromycin. Separation of the naturally fused modules 1 and 2 reduced pikromycin production more than 1000-fold 82 . Conversely, fusion of the naturally in trans polypeptides DEBS1 and DEBS2, or DEBS2 and DEBS3, maintained or even enhanced erythromycin production relative to the wild type 83 .…”
Section: Protein-protein Interactions During Intermediate Transfer Bementioning
confidence: 99%
“…Trans -AT PKSs lack the N- and C-terminal docking domains (NDD and CDD regions) that noncovalently connect ACP and KS domains in cis -AT systems (Weissman 2006; Yan, 2009; Whicher, 2013). The split nature of dehydrating bimodules is representative of many uncharacterized disconnections between trans -AT polypeptides.…”
Section: Introductionmentioning
confidence: 99%
“…When successive modules operate from independent proteins, non-covalent association of C- and N-terminal docking domains promote protein-protein interaction of the upstream ACP and downstream KS (Gokhale et al, 1999) (Figure 1A). Docking domains, ACP dd at the ACP C-terminus of the upstream module and dd KS at the KS N-terminus of the downstream module, are essential to ensure correct transfer of polyketide chain elongation intermediates (Gokhale et al, 1999; Kittendorf et al, 2007; Kumar et al, 2003; Tsuji et al, 2001; Weissman, 2006a, b; Wu et al, 2002; Wu et al, 2001), and thus are essential structural elements for engineering these pathways to generate novel small molecules by rearrangement or recombination of PKS modules (Menzella et al, 2007; Menzella et al, 2005; Reeves et al, 2004; Yan et al, 2009). Although early studies demonstrated that cognate docking domains can facilitate intermediate transfer between modules that do not naturally associate (Menzella et al, 2007; Menzella et al, 2005; Reeves et al, 2004; Wu et al, 2002; Yan et al, 2009), none of the systems explored docking domain structure and function across broad phylogenetic groups.…”
Section: Introductionmentioning
confidence: 99%